The Internet of Tall Buildings - Nieto-Chaupis, Huber (2022)
As seen in the event at Surfside, Miami FL, the permanent surveillance of tall buildings might to require the conjunction of the telecommunications technologies that in a side are offering accuracy in various levels of prediction, and on the other side are flexible to be operated to distance. In fact. in this paper, a novel Internet is proposed, it is called the Internet of Tall Buildings whose main purpose is to carry out in an unstoppable manner the precise measurement of small angular deviations. With this its is expected a kind of instantaneous radiography of spatial displacements of the vertexes of ceiling in a chain of tall buildings. Thus, whereas there is a sensing in one of them, then the wireless system will emit alerts and alarms at the cases that deviations beyond the allowed are registered.